The Impact of Community Attitudes on Environmental Sanitation Conditions in the Settlements of Mount Pala (Case Study in Mount Pala, Keteguhan Village, Teluk Betung Timur District, Bandar Lampung City) - Arif Setiajaya; Bambang Prasetio; Aulia Annas Mufti; Erlina Kurianingtyas; Nova Sari (Journal of Multidisciplinary Academic, 2023)
The environment, people's attitudes, and socioeconomic traits that have an impact on the physical state of the environment are the variables that have the biggest impact on the community's health status. Sanitation factors in efforts to enhance people's welfare in areas including health, way of life, settlement environmental conditions, and level of comfort. The research aims to identify characteristics; Analyze environmental sanitation conditions; Analyze the impact of behavior; and provide recommendations to the community regarding environmental sanitation conditions. The research location is Jalan Laksamana RE Martadinata, Keteguhan Village, Teluk Betung Timur District, Bandar Lampung City. This research method is quantitative descriptive with a method based on the philosophy of positivism. The results of the study are (1) Based on the results obtained on the socio-demographic characteristics of the community, it consists of 6 characteristics, namely gender, age, educational strata, type of work, income, and length of residence. (2) the results of the reliability test in the measurement instrument are categorized as high reliability, stating that the sanitation conditions in the settlement have very high problems. (3) The results of moderate reliability state that some people care, and some don't care about the environment. (4) Based on the results of field observations obtained a recommendation that can be carried out for the community, namely recommendations in the form of short-term socialization and long-term counseling related to the importance of maintaining clean sanitation and fostering a sense of care for the environment.